Bioactive food foams stabilized by licorice extract/whey protein isolate/sodium alginate ternary complexes. (May 2022) - Nooshkam, Majid; Varidi, Mehdi; Alkobeisi, Fatemeh
Abstract: Interactions among multi-component food matrices play a key role in modulating the foam properties. In this study, foams containing mixtures of sodium alginate (ALG; 0.5, 1.0, and 1.5% w/v), whey protein isolate (WPI; 0.2 and 0.6% w/v), and licorice extract (LE; 0.1, 0.3, and 0.5% w/v) were formed and characterized. The interactions between the components were confirmed by turbidity, ζ-potential, particle size, Fourier transforms infrared spectroscopy, and sodium dodecyl-sulphate gel electrophoresis. The pre-foam dispersions adopted a shear-thinning behavior with high apparent viscosity as a function of ALG level. Surface tension results indicated that ALG and LE were the main components at the air/water interface, and the pre-foam dispersions possessed a good antioxidant activity (up to 56.53%). The ALG/WPI/LE foamed systems had up to 446.03% overrun, up to 81.69% air-volume fraction, and up to 40.80 h physical stability. Foams with higher overrun and air-volume fraction displayed greater firmness and cohesiveness, as well. Additionally, the elastic properties (Gʹ) were superior to the viscous ones (Gʹʹ) at all frequency range which indicated the solid-like behavior of the foams. A remarkable free radical scavenging activity (up to 49.66%) was also observed in the foams. Therefore, the bioactive foams with high foamability, stability, and viscoelasticity could be used to design novel healthy aerated foods with low calorie content. Graphical abstract: Image 1 Highlights: Licorice extract/whey protein isolate/alginate based foams were produced. Licorice extract and alginate were the main components at air/water interface. The foams had high overrun, air-volume fraction, and physical stability. The foams had an elastic behavior (Gʹ > Gʹʹ) with high firmness and cohesiveness. Free radical scavenging property of the food foams was confirmed.